Day-case pelvic osteotomy for developmental dysplasia of the hip. (December 2020) - Moore, Dave M.; Sheridan, Gerard A.; Kelly, Paula M.; Moore, David P.; McCarthy, Kevin F.
Abstract: Purpose: In this article we report the results of a pilot study analysing the implications of performing pelvic osteotomies for developmental dysplasia of the hip (DDH) as a day case. We assess the advantages of performing paediatric pelvic osteotomies as day-case procedures from a financial perspective and from an in-patient bed resource point of view. Methods: This was a prospective cohort study analysing Salter and Pemberton pelvic osteotomies performed for DDH over a three-year period from 1st January 2017 to 30th September 2019. All patients residing within 50 km of the hospital were eligible for day-case procedures. All other cases were performed as in-patients. A detailed financial costing analysis was performed and the in-patient resources utilized were documented and compared between the two models of care. Results: In total, 84 Salter and Pemberton osteotomies were performed between 1st January 2017 to 30th September 2019. Of these cases, 35 were performed as day-case procedures. A total reduction in 70 in-patient bed days was reported. Total costs for a single in-patient requiring two nights of admission amounted to €5, 752, whereas the discharge cost of a day case was reported at €2, 670. The savings made by our institution amounted to €3, 082 per day case. A total saving of €102, 696 was made over three years. In all, seven day-case patients re-attended due to inadequate pain control. They required overnight admission and were discharged uneventfully the following day. Conclusion: Day-case pelvic osteotomies significantly reduce the number of in-patient bed days used in an elective paediatric orthopaedic setting. Significant financial savings in excess of €3, 000 per case are possible. The introduction of day-case pelvic osteotomy procedures can significantly improve the cost-effectiveness of managing DDH provided there are clear protocols in place with close clinical follow-up. Level of evidence: IV